Research protocol: On farm field trials to improve mungbean productivity through fertilizer management - Hossain, Md Khaled; Saleh Mohammad Shahriar; Atikuzzamman, Md; Gathala, Mahesh K.; Laing, Alison M. (International Maize and Wheat Improvement Center, 2023)
Mungbean is an important pulse crop in Bangladesh, where it is primarily grown in the south by small and marginal farming households who produce two-thirds of the total national mungbean crop. Mungbean is a short-duration crop which requires only 60-65 days from planting to harvest. It is typically grown between February and May with few inputs or intensive management, and is thus growing in popularity in southern Bangladesh. Yields of mungbean grown in farm fields are typically lower than those observed in research trials, largely because farmers apply little or no chemical fertilizer (certainly less than is recommended by government agencies). This reflects farmers’ general risk aversion, difficulty accessing appropriate fertilizers, and also increases in fertilizer prices as a result of international challenges in supply. Another potential option to improve mungbean yields is the inoculation of seed with rhizobium prior to sowing. This practice has been shown by the Bangladesh Agricultural Research Council (BARC) to produce high mungbean yields in Bangladesh without the addition of nitrogen fertilizer by accelerating biological nitrogen fixation (the addition of recommended doses of non-nitrogen fertilizers are still recommended). However farmers’ use of rhizobium has so far been limited due to lack of awareness of the benefits of its use, and ability to store it suitably prior to use. Additionally, there has been little work in Bangladesh on the response of rhizobium inoculum in mungbean cultivars. Mungbean is typically grown following wet-season (kharif II) rice cultivation and, over a number of years, mungbean may help to improve soil quality by fixing nitrogen within the soil and improving a soil’s physical, chemical and biological properties. Nevertheless it is likely that additions of fertilizer and/or rhizobium in mungbean crops will improve farmers’ overall cropping system yields, and potentially, profits. Under Work Package 1 of the CGIAR Asian Mega Deltas Initiative, CIMMYT is conducting on-farm trials in southern Bangladesh over two years to improve mungbean yields through improved fertilizer management practices and thus to improve the productivity and profitability of ricemungbean cropping systems. This protocol describes the field trials which are being conducted.